Patients With First-Time or Recurrent Patellar Dislocation Have a Similar High Rate and Extent of Articular Cartilage Injury Observed on Magnetic Resonance Imaging - Andres R. Perez, B.A.; Carlo Coladonato, B.S.; John Hayden Sonnier, M.D.; Samuel T. Saucedo, B.S.; John P. Avendano, B.S.; John Corvi, M.D.; Mike Campbell, M.D.; Fotios P. Tjoumakaris, M.D.; Steven B. Cohen, M.D.; Michael C. Ciccotti, Jr., M.D.; Kevin B. Freedman, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2024)
Purpose: To use magnetic resonance imaging (MRI) scans to compare the prevalence of articular cartilage damage in patients with a single patellar dislocation versus those with multiple dislocations and to compare the locations and severity of chondral injury between the groups. Methods: Patients with patellar dislocation between January 2017 and July 2021 were retrospectively identified. Patients with a documented history of patellar dislocation and an MRI scan of the affected knee were included. Patients with articular cartilage injury prior to the dislocation event were excluded. Articular cartilage injury was graded using a validated system: AMADEUS (Mean Total Area Measurement and Depth & Underlying Structures). Caton-Deschamps Index (CDI) scores and Dejour classifications of trochlear dysplasia were also collected. Data were calculated by performing t tests, Mann-Whitney tests, and χ2 or Fisher Exact tests to calculate P values for categorical data. Results: In total, 233 patients were included: 117 with primary dislocations and 116 with recurrent dislocations. Articular cartilage injuries were present in 51 patients with primary dislocations (43.6%) and 68 patients with recurrent dislocations (58.6%, P = .026). On comparison of the groups, the recurrent group contained a significantly larger proportion of female patients (65.5% vs 46.2%, P = .004). There was no difference in lesion size, subchondral bone defect, presence of bone edema, or total AMADEUS score between groups (P = .231). Caton-Deschamps Index scores were not significant when comparing between groups; however, the Dejour classifications showed higher grades in the recurrent group (P = .013 for A-D grading scale and P = .005 for high/low grading scale). Subgroup analysis revealed that when cartilage damage was present, patients from the primary group had significantly more full-thickness lesions (P < .001) and lower AMADEUS scores (P = .016). Conclusions: There was a similarly high prevalence of cartilage injury seen on MRI after both a primary patellar dislocation and a recurrent patellar dislocation. Chondral injury primarily affected the medial and lateral patellar facets and the lateral femoral condyle in both the primary and recurrent dislocation groups. However, the primary group showed an increased number of full-thickness lesions. There was no difference in lesion size, subchondral bone defect, presence of bone edema, or total AMADEUS score between the primary and recurrent groups. Level of Evidence: Level III, retrospective comparative prognostic investigation.